2022
DOI: 10.1037/rep0000447
|View full text |Cite
|
Sign up to set email alerts
|

The longitudinal development of posttraumatic growth among U.S. adult burn injury survivors.

Abstract: Purpose: Posttraumatic growth is the phenomenon of positive change resulting from coping with challenging or traumatic events. This study examines posttraumatic growth (PTG) in adult burn injury survivors via growth trajectories and correlates across time. Research Method: Three-hundred forty-eight burn injury survivors aged 19-86 years old completed a self-report measure of posttraumatic growth at 6, 12, and 24 months. An unconditional and conditional growth curve model with predictors were fitted to the post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Kornhaber et al's (2015) integrative review showed that burn survivors obtained positive insights, coping strategies, self‐awareness, personal growth, and improved quality of life. Quantitative studies have also shown that burn survivors experience posttraumatic growth after sustaining a burn injury (Hokes & Adams, 2022; Park & Lee, 2022). Posttraumatic growth, as a positive psychological experience for burn survivors, not only has positive impact on individuals' mental health, but can also reduce the stress caused by burn injury, motivate individuals to face the traumatic event with more positive coping styles (Kobosko et al, 2021), and ultimately promote physical and psychological recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Kornhaber et al's (2015) integrative review showed that burn survivors obtained positive insights, coping strategies, self‐awareness, personal growth, and improved quality of life. Quantitative studies have also shown that burn survivors experience posttraumatic growth after sustaining a burn injury (Hokes & Adams, 2022; Park & Lee, 2022). Posttraumatic growth, as a positive psychological experience for burn survivors, not only has positive impact on individuals' mental health, but can also reduce the stress caused by burn injury, motivate individuals to face the traumatic event with more positive coping styles (Kobosko et al, 2021), and ultimately promote physical and psychological recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal studies that focused on the trajectory of PTG among victims of disasters have shown findings that are inconsistent and complex. A few studies have shown that PTG does not change over time among disaster workers, burn injury survivors, victims of a major fire, and victims of two major earthquakes (Hokes & Adams, 2022; Linley & Joseph, 2006; E. M. Marshall et al, 2015; Thompson, 1985).…”
mentioning
confidence: 99%